2021
DOI: 10.3390/su131810328
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Global Expansion: A Study on Food and Beverage Franchisors in Malaysia

Abstract: In the past decade, franchising has become a well-known platform for business expansion. Various strategies have been employed by franchisors in expanding their business into the global market. However, few studies have assessed the determinants that can be adopted by the franchisors in bringing value as well as opening up opportunities for global market expansion. This study aims to explore the determinants of global expansion based on Malaysian franchisors’ experience. A qualitative research approach was ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Oh et al [62] described purchase intention as a determinant of buying behavior, as well as the consumer's willingness to purchase a particular product. Various factors affect purchase intention, such as personal values, lifestyles, food consumption values, brand image, attitudes, service quality, product selection attributes, and satisfaction [63][64][65][66]. Accordingly, industrial circles such as companies strive to understand purchase intentions from a marketing perspective, and related studies use it as a key variable for consumer behavior and business performance measurement [67].…”
Section: Product Reliability and Purchase Intentionmentioning
confidence: 99%
“…Oh et al [62] described purchase intention as a determinant of buying behavior, as well as the consumer's willingness to purchase a particular product. Various factors affect purchase intention, such as personal values, lifestyles, food consumption values, brand image, attitudes, service quality, product selection attributes, and satisfaction [63][64][65][66]. Accordingly, industrial circles such as companies strive to understand purchase intentions from a marketing perspective, and related studies use it as a key variable for consumer behavior and business performance measurement [67].…”
Section: Product Reliability and Purchase Intentionmentioning
confidence: 99%
“…This is a way for organizations to achieve business success, stay competitive in the digital market and ultimately contribute to the country's economy. In fact, the encouragement of entrepreneurs to engage in business development improves their chances of survival in a saturated market [3][4][5][6]. Previous studies have proved that entrepreneurial orientation (EO) is an effective tool that assists organizations in maintaining their performance [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Hew (2016), learning aspects such as pedagogical, social, managerial, and technical, which contribute to the construction, processing, and enhancement of knowledge, as well as engaging participants in learning can also be provided via online (Hew, 2016). In other words, both conventional and online approaches can benefit from online platforms by engaging in mutual interactions through discussion forums, peer-review feedback, cooperation in group work, and exchanging individual information via online platform that will enhance learning performance (Abd Aziz et al, 2021;Huisman et al, 2018;Kurucay & Inan, 2017;Ramdan et al, 2021). As these studies concluded, both learner-learner and learner-instructor interactions have a positive impact on learning that is measured based on greater learning outcomes.…”
Section: Online Learning Supportmentioning
confidence: 99%